The relationship between office environment and job satisfaction among employees at Tenaga Nasional Berhad (TNB) Kota Bharu Kelantan / Maisarrah Aqlili Riana Mohamad Zaini - Mohamad Zaini, Maisarrah Aqlili Riana (2015)
The purpose of this study is to identify the relationship between office The selected organization is employees at Tenaga Nasional Berhad(TNB) Kota Bharu, Kelantan. This correlation research was to determine that there is an existence of correlation between these environment and Job satisfaction among employees. variables. The sampling frame for this research will be obtain from the list of all employees from the Department of Human Resource Management, at Tenaga Nasional Berhad (TNB) Kota Bharu Kelantan with population of 150 employees and by using stratified sampling techniques, 150 respondents were made as sample size and 104 respondents has given feedback. In addition, the internal consistency using Cronbach's Alpha are also use to verify the measurement used later. The unit of analysis is individual with the instrument of Five(5) Likert Scale question. Therefore, questionnaire is used to collect the data and Statistical Package for Social Science (SPSS) version 20.0 is used to compute the correlation of the variables. This research should make a contribution to the understanding of the relationship between office environment and job satisfaction for most organizations in any industries, either government sector, private sector, body statutory and employee themselves. The result of the research shows that the variables are positive correlated with one other thus the hypothesis were accepted.